Application of Schiff bases derived from carboxymethylcellulose sodium in the separation of polysaccharides from kelp. Issue 6 (3rd March 2020) - Dai, Yunliang; Row, Kyung Ho
Abstract: BACKGROUND: A novel and rapid method for the separation and simultaneous extraction of two types of polysaccharides from kelp was developed using an ultrasonic‐assisted solid–liquid extraction method. Many polysaccharides obtained from diverse plant sources have important properties, such as anticancer, antioxidant and antitumor activities. Edible brown algae contain many bioactive compounds, including polysaccharides, vitamins and minerals. As the most common brown alga on the coastal areas of the Korean peninsula, kelp was selected to extract laminarin and fucoidan. Using ethanol as a solvent, the effects of ultrasonic‐assisted solid–liquid extraction on the extraction of polysaccharides from kelp, such as the extraction period, temperature, pH and mass:solvent ratio were investigated by high performance liquid chromatography. RESULTS: Compared to traditional heating and microwave‐assisted extraction methods, ultrasonic‐assisted solid–liquid extraction produced higher extraction yields in a shorter time. The optimal conditions for the ultrasonic‐assisted solid–liquid extraction supporting the highest recoveries of the two polysaccharides were 40 °C, ethanol as a solvent at pH 6, 40 min and a 1:30 g mL −1 mass:solvent ratio. Under the optimal conditions, the recoveries of fucoidan and laminarin were 94.29% and 88.90%, respectively. The real quantities of fucoidan and laminarin extracted from kelp with synthesized carboxymethylcellulose sodium Schiff bases added to ethanol in the proposed method were 120.7 ± 0.26 and 45.3 ± 0.19 mg g −1, respectively. CONCLUSION: Ultrasonic‐assisted solid–liquid extraction not only improved the recoveries of the extraction, but also was an eco‐friendly, efficient and promising alternative method for the simultaneous extraction of polysaccharides from kelp. © 2020 Society of Chemical Industry